PENDIDIKAN AKHLAK ANAK DALAM KELUARGA PETANI - Ira Nur Laili Isnani; Sri Haryanto; Muhtar Sofwan Hidayat (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to identify the moral values taught, the teaching methods used, and the outcomes of moral education within farmer families in Dusun Diwekan, Glapansari Village, Parakan Sub-district, Temanggung Regency. The study employs a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation, with primary data obtained from interviews with parents and children aged 6–10 years, and secondary data from supporting documentation. The findings indicate that the moral values taught include honesty, politeness, respect for parents, responsibility, and diligence in worship. These values are conveyed through exemplary behavior, habituation, advice, and the involvement of children in religious activities such as Qur’an recitation at the local TPQ. The moral education provided shapes children’s behavior to become more polite, obedient, responsible, and diligent in worship, both within the family environment and in the broader community.